2021
DOI: 10.3390/ijms22020962
|View full text |Cite
|
Sign up to set email alerts
|

The Bioavailability, Extraction, Biosynthesis and Distribution of Natural Dihydrochalcone: Phloridzin

Abstract: Phloridzin is an important phytochemical which was first isolated from the bark of apple trees. It is a member of the dihydrochalcones and mainly distributed in the plants of the Malus genus, therefore, the extraction method of phloridzin was similar to those of other phenolic substances. High-speed countercurrent chromatography (HSCCC), resin adsorption technology and preparative high-performance liquid chromatography (HPLC) were used to separate and purify phloridzin. Many studies showed that phloridzin had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 106 publications
1
34
0
Order By: Relevance
“…From natural sources, dihydrochalcones are isolated as aglycones and their glycosides.Most extensively described dihydrochalcones are phloretin and its 2 -O-glucoside named phloridzin, isolated from a genus of small trees and shrubs Malus. Many studies proved numerous biological activities of phloridzin, such as anti-diabetic, anti-inflammatory, anti-oxidant, antihyperglycemic, antimicrobial, cardio-and hepatoprotective, anti-obesity and others [18][19][20][21][22]. Similar activities have been reported for phloretin [23].…”
Section: Introductionsupporting
confidence: 55%
“…From natural sources, dihydrochalcones are isolated as aglycones and their glycosides.Most extensively described dihydrochalcones are phloretin and its 2 -O-glucoside named phloridzin, isolated from a genus of small trees and shrubs Malus. Many studies proved numerous biological activities of phloridzin, such as anti-diabetic, anti-inflammatory, anti-oxidant, antihyperglycemic, antimicrobial, cardio-and hepatoprotective, anti-obesity and others [18][19][20][21][22]. Similar activities have been reported for phloretin [23].…”
Section: Introductionsupporting
confidence: 55%
“…Although the DHCs could be found in flesh and peel, the highest concentration is located in the seeds, ranging from 24.1 to 86.4 mg/100 g FW [ 8 ]. Numerous studies have shown that both phloridzin and phloretin exert antibacterial, anti-inflammatory, antihyperglycemic, anti-diabetic and anticancer activities, and cardioprotective, neuroprotective hepatoprotective, and immunomodulatory properties [ 81 , 82 , 83 ].…”
Section: Effects Of Processing and Storage Conditions On The Stability Of Polyphenolsmentioning
confidence: 99%
“…Phlorizin is a natural dihydrochalcone found in a number of fruitful trees, mainly the Malus genus. It produces renal glycosuria and blocks intestinal and renal glucose reabsorption by inhibiting the sodium-glucose symporters located there [ 11 , 12 ]. Recently, ertugliflozin arrived as the newest synthetic GLT-2 (glucose transporter-2) inhibitor to receive FDA approval for the treatment of diabetes [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%